TALKING THERAPY TO REDUCE AUDITORY HALLUCINATIONS IN SCHIZOPHRENIA PATIENTS: A CASE STUDY AT SOCIAL REHABILITATION - Nuril Hikmah; Bagus Dwi Cahyono; Nurul Huda; Ronal Surya A; Apriana Rahmawati; Evy Aristawati (Department of Nursing, Faculty of Medicine, Universitas Sriwijaya, 2026)
Schizophrenia is a serious mental disorder characterized by perceptual changes, including auditory hallucinations. Non-pharmacological interventions are needed to help patients manage these symptoms. This case report describes nursing care for two schizophrenia patients with auditory hallucinations using talking therapy. Assessment was conducted on two patients at the Social Rehabilitation Unit through interviews and observations. The nursing diagnosis established was sensory perception disturbance: auditory hallucinations. Planning involved implementing talking therapy interventions based on Indonesian Nursing Intervention Standards. The intervention was conducted once daily for three consecutive days, with each session lasting approximately 30 minutes. Results showed a decrease in hallucination frequency in both patients after three days of intervention. Patient one showed significant improvement in using conversation as a distraction, while patient two showed reduced response to commanding hallucinations. Talking therapy showed improvement in reducing auditory hallucinations by shifting focus from internal stimuli to external reality through social interaction.